If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying w + -4w + -32 = 0 Reorder the terms: -32 + w + -4w = 0 Combine like terms: w + -4w = -3w -32 + -3w = 0 Solving -32 + -3w = 0 Solving for variable 'w'. Move all terms containing w to the left, all other terms to the right. Add '32' to each side of the equation. -32 + 32 + -3w = 0 + 32 Combine like terms: -32 + 32 = 0 0 + -3w = 0 + 32 -3w = 0 + 32 Combine like terms: 0 + 32 = 32 -3w = 32 Divide each side by '-3'. w = -10.66666667 Simplifying w = -10.66666667
| 4t=21 | | 2p^2+2p-9=0 | | 2x-y-1=o | | 0.045=x | | 0.5x-3=0.8 | | 2(x+2)-6=5x+1 | | 9k-2k+3k-6k=12 | | x-75/7.5=y | | 2(2w+7)=2w+7 | | y=.33(9x-18) | | 2a+7a+13a+(-5a)-15a-4=-10 | | 6=1/12x | | 3x-14/4=x-8 | | 5x+35=13x-5 | | 6x=12.24 | | 0.166x+2=0.33 | | 3x+(2x-6)=91.50 | | X-3(x-2)=7x-1(2x+5) | | -16x^2+44x+18=0 | | X(x+3x)=28 | | 2(4b+8)=4+6b | | 3t-(-12t)-15t+(-20t)-(-8)=-12 | | -5(1-(-25))+5((-8(-5))-2)=-4(-5)-8(-5) | | 0.25x-3=0.4 | | 27x+6=87 | | j-18=3 | | (6x^2-3x-10)/(x-8) | | Bx-2b=7x | | 125-3x=37 | | 5x+8=3x+3-2x-5 | | 2x+12-(3-5x)=15x-7 | | 13x+4x-15x-2x+x-1=8 |